Analysis of Enterpreneurial Intent in Vocational High School Students Based on a Review on Contextual, Background, and Personal Characteristics - Ahmad Fauzi; Indah Widiastuti; Suharno Suharno (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2022)
The high unemployment rate in Indonesia was dominated by vocational high school graduates approximately 8.63% of the 6.82 million. Therefore, to counter the circumstance, more entrepreneurs are required to explore job creation opportunities. This research was aimed at identifying the effects of entrepreneurial activity, gender, parents, self-confidence, and motivation on the entrepreneurial intent of vocational high school students. This study uses a descriptive method with a quantitative approach. The sample in this study was 85 final-year students of a high school in Central Java. A set of questionnaires was administered to explore the relationship between entrepreneurial intent and other contextual factors. The data derived from the survey were analyzed by correlation analysis and multiple regression. The results showed a positive and significant effect on entrepreneurial activity, self-confidence, and motivation, with regression coefficients of 0.056, 0.098, and 0.083, respectively. These three variables separately exhibited zero significance. Meanwhile, gender indicated a negative and major influence, with a regression coefficient of -0.171 and a significance level of 0.006. However, parents were not able to demonstrate any effect but recorded a regression coefficient of 0.176. Thus, entrepreneurial activity, self-confidence and student motivation may affect the intention to be an entrepreneur. It is expected that this study could be a reference in developing students' entrepreneurship intent.